Adverse Selection Effect for South Asian Countries in FTA Formation: An Empirical Study on the Determinants of FTA among the Bilateral Trading Partners - Jayathilaka, Ruwan; Keembiyahetti, Nandasiri (South Asia economic journal (Institute of Policy Studies), 2009)
This study examines the economic and non-economic factors governing the decision of forming Free Trade Agreements (FTAs) between two non-zero trading partners by estimating a Probit model using 9,178 country pairs having 705 active and operational bilateral FTAs. This study works on the implied hypothesis that FTA is an endogenously determined variable dependent on a number of economic and non-economic factors which are usually omitted from gravity type trade models. The study finds economically important and statistically significant evidences that the likelihood of forming an FTA by a pair of countries is positively related to the economic mass of the partners, similarity in economic size, differences of relative factor intensity, political stability, past import tariffs and the existence of FTAs in the close neighbourhood, whereas it is negatively related to the distance, economic remoteness and geographic continuity. Based on these findings, this study provides a good explanation as to why South Asian Association for Regional Cooperation (SAARC) countries are still far behind the FTA negotiation process and how SAARC countries are subject to adverse selection effect by rest of the world.